Análise de técnicas de modelagem matemática da evolução da microestrutura aplicada à laminação a quente de aços microligados ao Nióbio - Felipe Monteiro Moraes de Moura Bastos (2016)
Mathematical modeling has been used as an efficient and important tool in the study of the austenite microstructure behavior in hot rolling process. The mathematical modeling allows a proper understanding of the complex variables involved during the thermomechanical process of steels and its influence on the austenite grain evolution. There are basically two approaches to the mathematical modeling of the austenite grain evolution during the hot rolling process: the first one considers a mean grain size entering each pass, and the second one considers a grain size distribution entering each pass. Each of these approaches has particularities that influence directly its application and accuracy. Analyses of these two kinds of modeling were conducted in this work. Computational codes were developed based on the latest works published in the literature that represents each model. The codes were, then, validated and applied to industrial cases of hot rolling with data published in the literature. The behavior, advantages and disadvantages of each model were discussed.